SilverTix: connecting our elderly communities - Goh, Alicia Qiao Hui (Nanyang Technological University, 2024)
SilverTix is a web application which seeks to promote interactions between elderly members in our community, both in-person, as well as in the online space. This application aims to act as a platform for these senior members to discover common activities or develop new hobbies they may enjoy with their peers.